Cytotoxic T-lymphocyte reactivity with individual Sendai virus glycoproteins. - Al-Ahdal, M N (1985)
Liposomes were constituted with affinity-purified Sendai virus glycoproteins HN and F and phosphatidylcholine (PC) or phosphatidylethanolamine: phosphatidylserine (PEPS). The glycoprotein-bearing recombinant vesicles (RV) were used to modify the surface of P815 mastocytoma cells (H-2d) or EL4 lymphoma cells (H-2b). The cells treated with HN-F-PCRV, HN-PEPSRV, or F-PEPSRV were shown by surface immunofluorescence to retain antigen for at least 2 h at 37 degrees C after treatment. The modified cells were used in cytotoxicity assays with effector spleen cells from either DBA/2 (H-2d) or C57BL/6 (H-2b) immunized by inoculation of active Sendai virus. Cells modified by treatment with HN/F-PCRV showed susceptibility to cytolysis similar to that in actively infected cells. Cells modified with HN-PEPSRV or with F-PEPSRV were also susceptible. The sum of reactivities of the anti-HN component and the anti-F components was close to that seen with HN- and F-bearing targets. Syngeneic but not allogeneic target cells expressing Sendai virus glycoproteins were bound and lysed by the effector cells, which was expected if the interactions were major histocompatibility complex restricted. The activity was attributed to cytotoxic T lymphocytes, since it was depleted by treatment with anti-Thy 1.2 antibody and complement.